PENGEMBANGAN KARAKTER CERDAS MELALUI BIMBINGAN DAN KONSELING PADA ANAK USIA DINI DI TK ISLAM SARANA BHAKTI - Anggia Evitarini (Guidance and counseling the university of Prof. Dr. Hazairin. SH, 2019)
The intelligence of the nation's life is based on ability, character and character in the corridor of a dignified civilization. Thus the function of education to shape the character and civilization of the life of a dignified nation is expected to run properly. One effort to be able to build intelligent people is through the implementation of eclectic counseling, where the development of children at this age is the most important period (Golden Age) in the course of human life. Through eclectic counseling, researchers try to build intelligent characters in early childhood, especially those who are expected to support a positive personality towards the surrounding environment so that they can become future generations who are ready to build the life of the nation and state. The results showed that there was an increase in intelligent character in every early childhood in Islam Sarana Bhakti Kindergarten through the implementation of eclectic counseling.